2014
DOI: 10.1177/1461444814520873
|View full text |Cite
|
Sign up to set email alerts
|

The interface as discourse: The production of norms through web design

Abstract: This article elaborates a theoretical case for considering new media as productive power, viewing web interfaces as both reflecting and reinforcing social logics. It then details an analytic method for websites -discursive interface analysis -which examines functionalities, menu options, and page layouts for the structures at work within them. The piece concludes with a short, illustrative examination of several official media company websites, articulating the productive constraints of their interfaces and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 26 publications
0
78
0
8
Order By: Relevance
“…Such an analysis asks: -Which are the paths of least resistance and why, given the circumstances? (Stanfill 2015). This is essentially a matter of identifying the salient dispositions and contingencies through which an affordance operates on an actor.…”
Section: Affordance Opportunities and Constraintsmentioning
confidence: 99%
“…Such an analysis asks: -Which are the paths of least resistance and why, given the circumstances? (Stanfill 2015). This is essentially a matter of identifying the salient dispositions and contingencies through which an affordance operates on an actor.…”
Section: Affordance Opportunities and Constraintsmentioning
confidence: 99%
“…In the software studies literature, affordances are usually observed through active use, for example in the case of norms and values communicated through interface design (Stanfill, 2015), or, as demonstrated by Bucher and Helmond (2018), by evaluating user comments. However, complementary to these earlier studies, this article suggests considering the evolution of software affordances over time, including software versions that can no longer be experienced first hand.…”
Section: Towards a Diachronic Perspective On Software Affordancesmentioning
confidence: 99%
“…Affordances are features (material and semiotic) that constrain the ways that technology might be designed and configured, as well as interpreted by users (Hutchby 2001). Stanfill (2015) argues that affordances draw on Foucauldian notions of productive power to make "normative claims" about the purpose and appropriate use of the technology, building a set of interpretive possibilities into the interface. The normative claims work to establish a "cultural common sense" about the users of the interface (Stanfill 2015).…”
Section: Interface Analysismentioning
confidence: 99%
“…Stanfill (2015) argues that affordances draw on Foucauldian notions of productive power to make "normative claims" about the purpose and appropriate use of the technology, building a set of interpretive possibilities into the interface. The normative claims work to establish a "cultural common sense" about the users of the interface (Stanfill 2015).…”
Section: Interface Analysismentioning
confidence: 99%
See 1 more Smart Citation